Combinations of peptides synergistically activate the regenerative capacity of skin cells in vitro. (25th August 2021) - Flagler, Michael J.; Tamura, Makio; Laughlin, Tim; Hartman, Scott; Ashe, Julie; Adams, Rachel; Kozak, Kim; Cresswell, Kellen; Mullins, Lisa; Jarrold, Bradley B.; Isfort, Robert J.; Sherrill, Joseph D.
Abstract: Objective: To explore synergistic effects related to skin regeneration, peptides with distinct biological mechanisms of action were evaluated in combination with different skin cell lines in the presence or absence of niacinamide (Nam). Furthermore, the synergistic responses of peptide combinations on global gene expression were compared with the changes that occur with fractional laser resurfacing treatment, a gold standard approach for skin rejuvenation, to further define optimal peptide combinations. Methods: Microarray profiling was used to characterize the biological responses of peptide combinations (+/− Nam) relative to the individual components in epidermal keratinocyte and dermal fibroblast cell lines. Cellular functional assays were utilized to confirm the synergistic effects of peptide combinations. Bioinformatics approaches were used to link the synergistic effects of peptide combinations on gene expression to the transcriptomics of the skin rejuvenation response from fractional laser treatment. Results: Microarray analysis of skin cells treated with peptide combinations revealed synergistic changes in gene expression compared with individual peptide controls. Bioinformatic analysis of synergy genes in keratinocytes revealed the activation of NRF2‐mediated oxidative stress responses by a combination of Ac‐PPYL, Pal‐KTTKS and Nam. Additional analysis revealed direct downstream transcriptional targets of NRF2/ARE exhibiting synergistic regulation by this combination of materials, which was corroborated by a cellular reporter assay. NRF2‐mediated oxidative stress response pathways were also found to be activated in the transcriptomics of the early skin rejuvenation response to fractional laser treatment, suggesting the importance of this biology in the early stages of tissue repair. Additionally, the second combination of peptides (pal‐KT and Ac‐PPYL) was found to synergistically restore cellular ATP levels that had been depleted due to the presence of ROS, indicating an additional mechanism, whereby peptide synergies may accelerate skin repair. Conclusion: Through combinatorial synergy studies, we have identified additional in vitro skin repair mechanisms beyond the previously described functions of individual peptides and correlated these to the transcriptomics of the skin rejuvenation response of fractional laser treatment. These findings suggest that specific peptides can act together, via complementary and synergistic mechanisms, to holistically enhance the regenerative capacity of in vitro skin cells. Abstract : Through combinatorial synergy studies, we have identified additional in vitro skin repair mechanisms beyond the previously described functions of individual peptides and correlated these to the transcriptomics of the skin rejuvenation response of fractional laser treatment. These findings suggest that specific peptides can act together, via complementary and synergistic mechanisms, to holistically enhance the regenerative capacity of in vitro skin cells. Résumé : Objectif: Pour explorer les effets synergiques liés à la régénération cutanée, les peptides ayant des mécanismes d'action biologiques distincts ont été évalués en association dans différentes lignées cellulaires cutanées en présence ou en l'absence de niacinamide (Nam). De plus, les réponses synergiques des associations de peptides sur l'expression des gènes globale ont été comparées aux changements qui surviennent avec le traitement de resurfaçage au laser fractionné, une approche de référence pour le rajeunissement de la peau, afin de définir davantage les associations optimales de peptides. Méthodes: Le profilage de micro‐réseau a été utilisé pour caractériser les réponses biologiques des combinaisons de peptides (+/‐Nam) par rapport aux composants individuels dans les lignées cellulaires de kératinocytes épidermiques et de fibroblastes dermiques. Des tests fonctionnels cellulaires ont été réalisés pour confirmer les effets synergiques des associations de peptides. Des approches bio‐informatiques ont été utilisées pour mettre en lien les effets synergiques des associations de peptides sur l'expression des gènes à la transcriptomique de la réponse de rajeunissement de la peau du traitement au laser fractionné. Résultats: L'analyse par micro‐réseau des cellules cutanées traitées par des combinaisons de peptides a révélé des changements synergiques dans l'expression des gènes par rapport aux contrôles peptidiques individuels. L'analyse bio‐informatique des gènes de synergie dans les kératinocytes a révélé une activation des réponses au stress oxydatif médiées par NRF2 par une association d'Ac‐PPYL, de Pal‐KTTKS et de Nam. Une analyse supplémentaire a révélé des cibles transcriptionnelles directes en aval de NRF2/ARE présentant une régulation synergique par cette combinaison de matériaux, qui a été corroborée par un test de gène rapporteur. Les voies de réponses au stress oxydatif médiées par NRF2 se sont également révélées activées dans la transcriptomique de la réponse précoce de rajeunissement cutané au traitement au laser fractionné, ce qui suggère l'importance de cette biologie dans les stades précoces de la réparation des tissus. De plus, une deuxième association de peptides (pal‐KT et Ac‐PPYL) s'est avérée restaurer de manière synergique les taux d'ATP cellulaire qui avaient été épuisés en raison de la présence de ROS, indiquant un mécanisme supplémentaire par lequel les synergies de peptides pourraient accélérer la réparation cutanée. Conclusion: Grâce à des études de synergie combinatoire, nous avons identifié des mécanismes de réparation cutanés in vitro supplémentaires au‐delà des fonctions précédemment décrites des peptides individuels et les avons corrélés à la transcriptomique de la réponse de rajeunissement de la peau au traitement au laser fractionné. Ces résultats suggèrent que des peptides spécifiques peuvent agir ensemble, par le biais de mécanismes complémentaires et synergiques, pour améliorer de manière globale la capacité régénérative des cellules cutanées in vitro.